Aprendizagem experiencial: um estudo com acadêmicos dos Cursos de administração do estado da Paraíba - Santos, Gabriela Tavares dos (2013)
The aim of this study is to analyze the contributions of experiences (social, professional and formal education) in the learning process of the Business Administration Course students, for all the public and private institutions in the state of Paraíba. And, the specific objectives: to characterize the experiences (social, professional and formal education) experienced by students during graduation in Business Administration; identify the contribution of experiences (social, professional and formal) in the learning process of undergraduate students in the Business Administration Courses, establish relations between the level of contribution of experiences (social, professional and formal) in the learning of undergraduate students. The theoretical framework was divided into seven parts: (i) self-directed learning, (ii) the concepts of andragogy and trends, (iii) experiential learning, (iv) the types of experiences with social experiences, professional and formal education (v) the process of skills development for the administrator, (vi) the role of experiential learning in higher education and (vii) the final thoughts on the chapter. The research is configured of qualitativequantitative nature, with an exploratory and descriptive type conducted in three stages: two through qualitative interviews and focus groups and the other as a quantitative, using a questionnaire. The qualitative-quantitative survey was developed by graduate students of a few Institutions of Higher Education from the state of Paraiba; the qualitative phases had the participation of 60 respondents and the quantitative phase had a sample of 410 participants. The interviews and focus groups were transcribed, filed and analyzed through content analysis and data interpretation. In the quantitative phase, data analysis relied on the SPSS, and subsidized the conduction of a descriptive analysis, relationship tests, correlation, factor analysis and ANOVA. 10 factors that characterize social experiences, professional and formal education, were identified and among these, the most significant are the professional action and academic activities. The results extend our understanding of the contributions of experiences in the learning process of students in administration courses, making it possible to say that professional experiences are the most significant ones, and then, the experiences of formal and social education. At the end, items that may compose an evaluation scale of the experiments on learning were suggested.